Cytokine mRNA profiles in bovine macrophages stimulated with Trypanosoma congolense - Kazuhiro, Y.; Agaba, Morris; Iraqi, F.A.; Naessens, Jan (2007)
It is known that different breeds of cattle display differential susceptibilities to Trypanosome congolense infections, and that N'Dama cattle remain more productive after infection than Boran cattle which are more susceptible to T. congolense. Macrophages from both breeds were cultured in vitro and the expressions of a number of cytokines and iNOS mRNA were analyzed using real time RT-PCR after stimulation with antibody-opsonized trypanosomes. No significant difference was seen between the responses of the two breeds. However, RNA levels of TNF-α in the IFN-γ-primed macrophages were about 100-fold higher than those in the non-primed macrophages. A significant ten-fold decrease was seen for the anti-inflammatory cytokine IL-10. These results indicate that priming of the cells with IFN-y cause a serious shift toward an inflammatory response.